PENGEMBAN TANAMAN STROBERI (Fragaria sp) SECARA ORGANIK PADA TANAH ANDISOL TAWANGMANGU - Teguh Supriyadi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta)
This research was influence to heighten yield of Stroberry (Fragaria sp) with organic fertilizer. The research had been conducted at Kalisoro, Tawangmangu, Karanganyar an altitude 1.100 m above sed level of with Andisol soil type, from March until September 2006. This research used factorial method with the basis method Randomyzed Camplotely Design, consicting of two factors 1) Kind organic fertilizer (M1= Cow manure, M2 = bokhasi) and 2) dosage of organic fertilzer (D0 = Control, D1 = 10 ton/ha, D2 = 20 ton/ha, D3 = 30 ton/ha) with three replications. The experiment showed: (1) Kind organic fertilizer very significans for fresh weight of crown , significans for number of tiller, number of flower, number of fruit; not significan for plant height, dry weight of crown and weight of fruit (2). Dosage organic fertilizer very significan for plant height, number of tiller, fresh weight of crown, and dry weight of crown, number of flower, number of fruit, weight of fruit per- plant. (3) Interaction kind organic fertilizer with dosage organic fertilizer very significant for plant height, number of tiller, fresh weight of crown, and dry weight of crown, number of flower, number of fruit, weight of fruit per- plant (4) Correlation with treatment positif to growth and yield parameter strowberry plant. (5) Heighten weight of fruits 69,90 g/plant (5,13 ton/Ha) for bokhasi fertilizer dosage 30 ton/ha (M2D3), and lowest weight of fruits 10,40 g/plant (0.92 ton/Ha) for without organic fertilizer.